2007
DOI: 10.1186/bf03352690
|View full text |Cite
|
Sign up to set email alerts
|

First results from the Penn State Allsky Imager at the Arecibo Observatory

Abstract: The Penn State Allsky imager (PSASI), a user-owned-public-access (UOPA) instrument installed at Arecibo Observatory (AO: 18.3 • N, 66.75 • W; altitude: 350 m a.s.l.; L = 1.43 at 300 km; dip angle: 46• ; geomagnetic coordinates: 29• N, 5.5• E), is a CCD-based high-resolution allsky optical imager that has been collecting ionospheric airglow data at night since May 2003. The computer controlled six-position filter wheel is equipped with three filters at 630 nm (red), 557.7 nm (green), and 777.4 nm (near-IR), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…From that and the correlation between Kp and plumes/depletion bands observed by PSASI (e.g. in Seker et al, 2007), it could be inferred that as the geomagnetic activity becomes more disturbed, it becomes more likely to observe equatorial plumes reaching AO latitudes instead of these MSTID bands. More studies on this need to be done in order to understand the dynamics of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From that and the correlation between Kp and plumes/depletion bands observed by PSASI (e.g. in Seker et al, 2007), it could be inferred that as the geomagnetic activity becomes more disturbed, it becomes more likely to observe equatorial plumes reaching AO latitudes instead of these MSTID bands. More studies on this need to be done in order to understand the dynamics of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Recent imaging studies have revealed that the mid-latitude F-region is also active with plasma depletion bands (or so called slabs, MSTIDs), equatorial plumes, the midnight temperature maximum, spread-F, etc. (Mendillo et al, 1997;Garcia et al, 2000;Kelley et al, 2000bKelley et al, , 2002Kelley et al, , 2004Shiokawa et al, 2003a, b;Otsuka et al, 2003;Seker et al, 2007). The use of imager and radar together has been the subject of several recent papers: Pi et al (2000) (imager, ISR, FPI), Kelley et al (2000a) (imager, ISR), Kelley et al (2002) (imager, ISR, GPS), Otsuka et al (2003) (imager, MU radar, FPI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and perhaps most importantly, it has been tentatively found that, at midlatitudes, the MSTIDs usually occur during geomagnetically quiet times [Saito et al, 2002;Shiokawa et al, 2003;Kotake et al, 2006;Tsugawa et al, 2007a;Candido et al, 2008;He and Ping, 2008;Seker et al, 2008] whereas the plumes usually occur at midlatitudes when the geomagnetic activity is high [Garcia et al, 2000;Sahai et al, 2000;Seker et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Since atomic oxygen is one of the major sources of ions and electrons in the lower E-region of the ionosphere, this emission can be used to monitor both neutral phenomena (such as gravity waves) and electrodynamics near this altitude. More details on PSASI, airglow, and ionospheric phenomena revealed by it can be found in Seker et al (2007).…”
Section: Methodsmentioning
confidence: 99%